2018
DOI: 10.1186/s13104-018-3238-4
|View full text |Cite
|
Sign up to set email alerts
|

Variability of phenolic and alkaloid content in different plant parts of Carissa edulis Vahl and Zanthoxylum chalybeum Engl.

Abstract: ObjectiveThe objective of the study was to investigate the relative abundance and effect of post-harvest treatment on total phenolics (TP) and total alkaloids in the leaves and bark of Carissa edulis and Zanthoxylum chalybeum, which would give an indication of the suitability of leaves as alternative sources of medicine in these plant species.ResultsResults indicated higher levels of total phenolics than total alkaloids in both of the species under both freezing and air drying conditions. While more alkaloids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
(60 reference statements)
2
21
0
1
Order By: Relevance
“…However, reports discussing the combined effects of drought and heat stress on the accumulation of secondary metabolites are rare. Accumulation of secondary metabolites, including isoprenoids, alkaloids, and phenolics, under stressful conditions occurs due to the oversupply of NADPH + H+ [72,74,75]. In the present study, both plant species exhibited significant accumulations of alkaloids, which presumably play similar roles in drought and heat tolerance as they do in other plants.…”
Section: Effects Of Drought and Heat Stress On The Growth And Physiolsupporting
confidence: 56%
“…However, reports discussing the combined effects of drought and heat stress on the accumulation of secondary metabolites are rare. Accumulation of secondary metabolites, including isoprenoids, alkaloids, and phenolics, under stressful conditions occurs due to the oversupply of NADPH + H+ [72,74,75]. In the present study, both plant species exhibited significant accumulations of alkaloids, which presumably play similar roles in drought and heat tolerance as they do in other plants.…”
Section: Effects Of Drought and Heat Stress On The Growth And Physiolsupporting
confidence: 56%
“…plant. Stress factors such as temperature, moisture and soil nutrients might be responsible for the dissimilarity in phenols content among different plant parts(de Matos Nunes et al, 2014;Nantongo et al, 2018). Differences in phenols content among the different plant part was reported previously.…”
mentioning
confidence: 70%
“…These results agree with the findings of Unuigbe et al (2014) which reported absence of alkaloids in leaves but present in seeds of M. oleifera. According to Nantongo et al (2018), the concentration of alkaloids can only be discovered in 20% of the plant species particularly in young, actively growing tissues. Therefore, the production and abundance of alkaloids are mainly related to factors that affect growth of fresh plant tissues such as light, soil nutrients and moisture, temperature and other physicochemical factors (Kirk et al, 2010;Desgagné-Penix, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of terpenoids seems to be very low in each plant part when compared to other compounds in plant samples collected from DRC and Kenya. Generally, in most plants the common order of secondary metabolites with respect to abundance is phenolics > alkaloids > cyanogenic glycosides > tannins > flavonoids and saponins > terpenoids (Nantongo et al, 2018). In addition, concentrations of terpenoids in plant tissues are regulated by the availability of substrate and the activity and type of biosynthetic enzymes.…”
Section: Discussionmentioning
confidence: 99%